Mini Review: Current Trends and Understanding of Exosome Therapeutic Potential in Corneal Diseases - Tiwari, Anil; Singh, Aastha; Verma, Sudhir; Stephenson, Sarah; Bhowmick, Tuhin; Sangwan, Virender Singh (Frontiers in Pharmacology, 2021)
Exosomes are a subset of extracellular vesicles (EVs) that are secreted by most cell types. They are nanosized EVs ranging from 30 to 150 nm. The membrane-enclosed bodies originate by the process of endocytosis and mainly comprise DNA, RNA, protein, and lipids. Exosomes not only act as cell-to-cell communication signaling mediators but also have the potential to act as biomarkers for clinical application and as a promising carrier for drug delivery. Unfortunately, the purification methods for exosomes remain an obstacle. While most of the exosome researches are mainly focused on cancer, there are limited studies highlighting the importance of exosomes in ocular biology, specifically cornea-associated pathologies. Here, we summarize a brief description of exosome biogenesis, roles of exosomes and exosome-based therapies in corneal pathologies, and exosome bioengineering for tissue-specific therapy.